Impact Of Shading Devices On The Thermal Performance Of Residential Building In Amman, Jordan - Abbaas, Esra’a Shehadeh Hussein (2023)
Cooling strategies during hot-dry summer in Amman, Jordan, consume a hefty amount of annual electrical energy. Exploiting natural sources to achieve a thermal comfort indoor environment in residential buildings would be a good practice. This work investigates the influence of external window shading devices configurations on the thermal performance and thermal comfort of three residential building forms, namely rectangular, L-shape, and U-shape, in Amman. The research starts with site measurements to validate the simulation data. For the simulation study the buildings’ models are designed using the SketchUp plugin OpenStudio and then plugged into the EnergyPlus simulator. The thermal performance of buildings is studied using indoor air temperature, mean radiant temperature, air speed, and relative humidity. The thermal comfort is evaluated according to ASHRAE-55 adaptive model and Fanger’s models. This study investigates the vertical, horizontal, and combined shading types of external window shadings at different lengths. It is found that the combination between vertical and horizontal shading of 1.25 m length has the best performance in minimizing indoor air temperature, and the vertical fins shading has minimal impact. In case of windows open with such strategies, the indoor air temperature is notably dropped up to 8.85 °C in the daytime and 12.04 °C at nighttime, which improves the thermal performance of all building forms. Combining shading and natural ventilation improves thermal comfort in all building forms, where the indoor thermal sensation shifts from hot, warm, and slightly warm to slightly warm, neutral, and comfortable, respectively.